The Integration of Technical Vocational Education and Training Systems to Expand Employment Opportunities and Business Development - Nuraeni, Yeni; Henigusnia, Henigusnia (Soegijapranata Catholic University, 2021)
Abstract: The high unemployment of vocational graduates in Indonesia shows that vocational system needs an improvement so it can produce competent workers and reduce the number of unemployed. This study aims to evaluate and analyze the Technical Vocational Education and Training (TVET) system in Indonesia which has not been integrated causing graduates find it difficult to get a job or develop a business. The approach used in this study is qualitative. The data collection conducted through in-depth interviews with key informants. The results of the study indicate that the TVET in Indonesia still involves various government and private institutions and does not yet have a good coordination mechanism and integrated programs. The improvement of the TVET system by developing an integration model involving government and the private institutions to develop the three main pillars, they are competency standards, competency-based training programs and competency certifications.Keywords: TVET, Competency based-training, Employment Opportunities